Comparison of Indonesian and Hungarian Laws Regarding Errors in Persona in Land Buying and Selling Transactions - Diana Setiawati; Widya Ayu Khairunnisa; Rofi Aulia Rahman (Universitas Muhammadiyah Surakarta, 2024)
ABSTRACT Purpose: This research aims to determine the comparison of legal implementation between 2 (two) countries that adhere to a civil law legal system in viewing the issue of error in person. With the main aim of providing insight and potential solutions to overcome the problem of default and error in person, this research contributes to solving the challenges encountered in this domain. Methodology: This research employed normative research methods through a case approach and a comparative approach, both for Indonesia and Hungary. Results: The results of this research demonstrated that the 2 (two) legal perspectives of Indonesia and Hungary both have quite significant similarities in viewing a default or error in person. The decision made by the judge in the decision above can actually still be prosecuted if the person concerned wishes to do so. However, it could be considered inaccurate and could be even more detrimental to the defendant. Hence, the legal considerations applied are deemed appropriate. Applications of this study: This research’s findings can be used to analyze legal comparisons between 2 (two) countries and the judge's considerations regarding error in persona in breach of contract disputes with Decision Number 59/PDT/2021/PT SMR. Novelty/Originality of this study: Undoubtedly, each country has a different view on issues that harm certain parties in the agreement or default; likewise, with formal defects in the form of errors in persona. Therefore, more in-depth research is needed on legal comparisons in 2 (two) countries and judges' considerations regarding errors in persona. Such research contributes to a comprehensive understanding of how legal systems address these issues, facilitating better decisions and potentially encouraging harmonization or convergence of legal practice across jurisdictions. Keywords: Agreement, Default, Error in persona ABSTRAK Purpose : Penelitian ini bertujuan untuk mengetahui komparasi pelaksanaan hukum diantara 2 (dua) negara yang menganut sistem hukum civil law dalam memandang persoalan error in persona. Dengan tujuan utama memberikan wawasan dan solusi potensial guna mengatasi masalah wanprestasi maupun error in persona. Penelitian ini sebagai kontribusi pada penyelesaian tantangan yang dihadapi dalam domain ini. Methodology : Penelitian ini menggunakan metode penelitian normatif melalui pendekatan kasus dan pendekatan komparatif, baik terhadap negara Indonesia ataupun Hungaria. Results : Hasil penelitian ini menunjukkan bahwa 2 (dua) perspektif hukum antara Indonesia dan Hungaria, keduanya memiliki kesamaan yang cukup signifikan dalam memandang suatu wanprestasi maupun error in persona. Pengambilan keputusan oleh hakim dalam putusan diatas sebenarnya masih bisa dituntut jika yang bersangkutan menghendakinya, akan tetapi dapat terbilang kurang tepat dan bisa saja semakin merugikan bagi pihak tergugat. Oleh karena itu, pertimbangan hukum yang diterapkan terbilang sudah tepat. Applications of this study : Hasil penelitian ini dapat digunakan untuk menganalisis terkait komparasi hukum diantara 2 (dua) negara dan pertimbangan hakim terkait error in persona pada sengketa wanprestasi dengan Putusan Nomor 59/PDT/2021/PT SMR. Novelty/ Orginalty of this study : Permasalahan yang merugikan pihak tertentu dalam perjanjian atau wanprestasi, tentunya dalam hal itu setiap negara memiliki pandangan yang berbeda. Begitu juga dengan cacat formil berupa error in persona. Oleh karena itu, diperlukan penelitian lebih mendalam terhadap komparasi hukum dalam 2 (dua) negara dan pertimbangan hakim terkait error in persona. Penelitian semacam itu guna berkontribusi pada pemahaman yang komprehensif tentang bagaimana sistem hukum menangani masalah ini, memfasilitasi keputusan yang lebih baik dan berpotensi mendorong harmonisasi atau konvergensi praktik hukum di seluruh yurisdiksi. Keywords: Perjanjian, Wanprestasi, error in persona